Biofilm Time-Kill Curves to Assess the Bactericidal Activity of Daptomycin Combinations against Biofilm-Producing Vancomycin-Resistant Enterococcus faecium and faecalis - Katie E. Barber; Zade Shammout; Jordan R. Smith; Razieh Kebriaei; Taylor Morrisette; Michael J. Rybak (Antibiotics, 2021)
Introduction: E. faecium and E. faecalis are responsible for 13.9% of hospital-acquired infections with frequent resistance to vancomycin (82.6% of E. faecium, 9.5% of E. faecalis). Medical device infections secondary to enterococci often require combination therapy due to impaired activity against biofilm embedded cells. In vitro data demonstrate synergistic activity of daptomycin combinations. Using a novel, biofilm time-kill approach, we evaluated whether daptomycin combinations maintained synergy against biofilm-producing E. faecium and E. faecalis. Methods: Broth microdilution (BMD) and biofilm MIC (bMIC) values for daptomycin, ampicillin, ceftriaxone, fosfomycin, and rifampin were determined against biofilm-producing E. faecium and E. faecalis. Daptomycin combination bMIC values were determined in the presence of biologic concentrations of other antimicrobials. Synergy was evaluated against two E. faecalis (R6981, R7808) and two E. faecium (5938 and 8019) using a previously described biofilm time-kill method. Synergy was defined as ≥2 log10 CFU/cm2 reduction over the most active agent alone. Bactericidal activity was defined as ≥3 log10 CFU/cm2 reduction. Results: Daptomycin bMICs were 2–8-fold higher than BMD. In the presence of other antimicrobials, daptomycin bMICs were reduced ≥ two-fold in dilutions. Ceftriaxone and ampicillin demonstrated the most potent combinations with daptomycin, yielding synergy against three of four strains. Daptomycin plus rifampin was synergistic against E. faecium 5938 and E. faecalis 6981 and produced bactericidal kill. The combination of daptomycin plus fosfomycin displayed synergy solely against E. faecalis 6981. Conclusions: Daptomycin combinations with beta-lactams demonstrated promising synergistic activity against both E. faecium and E. faecalis. While daptomycin plus rifampin yielded bactericidal results, the effect was not seen across all organisms. These combinations warrant further evaluation to determine the optimal dose and response.